Analisis Produktivitas Kerja Karyawan pada Departemen Logistik dengan Metode Regresi Linear Berganda di PT KLM - Kurnia, Iin; Safariyani, Eva; Sari, Rianita Puspa (Fakultas Teknik Universitas Tulang Bawang, 2026)
Over the past four months, PT KLM has experienced discrepancies between logistics delivery targets and actual performance, both through truck and train modes. This underachievement is suspected to be related to the suboptimal productivity of logistics staff due to weak leadership and an unsupportive work environment. This study aims to analyze the influence of leadership (X1) and work environment (X2) on the work productivity (Y) of logistics staff at PT KLM. A total of 60 respondents were selected using simple random sampling technique, and multiple linear regression was the methodology used. A questionnaire was utilized to collect data, and SPSS software was employed for analysis. The results indicate that partially, neither leadership nor work environment has a significant impact on productivity. However, simultaneously, both have a positive and significant impact on the productivity of logistics staff with an adjusted R square value of 10.3%. These findings highlight the importance of synergy between leadership and the work environment in enhancing productivity. In relation to these findings, strategies for improving operational performance need to focus on strengthening both aspects in an integrated manner. Keywords: Leadership, Productivity, Work Environment.